Enriching distance teaching and learning of undergraduate mathematics using videoconferencing and audiographics - Harman, Chris; Dorman, Marilyn (Distance education, 1998)
Technical subjects such as mathematics do not transfer easily to the distance education mode, so teaching and learning in such environments present special challenges. Any technologies employed for this purpose must satisfy the need for visual material, algebraic symbolism, and geometric representation. There should be opportunities to explore ideas, to work on problem solving and to provide specific feedback, preferably through prompt verbal and visual explanations. Most importantly, the medium should also facilitate the development of motivation, enthusiasm for the subject, and the potential for interactivity. An interactive teaching and learning model involving Desktop Videoconferencing (DVC) and other audiographic facilities was developed and trialled for distance education in undergraduate mathematics. It appears that very little has been reported previously in this area of mathematics teaching, certainly not on the scale of this development. Weekly teaching and learning sessions of two hours duration were held with a first-year group throughout the teaching semester. This experiment demonstrated that it was possible to integrate the systems used, together with computer applications/graphics software, to enable the difficult task of representing algebraic, geometric, and numeric concepts, all of which are essential for the development of higher level mathematical topics. Various qualitative measures were used for analysis of (i) complexity of the environment, (ii) effectiveness of the medium/methodology, (iii) improvement in skills, and (iv) the development of interactivity.